2020
DOI: 10.1039/d0pp00247j
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of 3D Bi2MoO6 microspheres with oxygen vacancies for enhanced visible-light photocatalytic activity

Abstract: Oxygen vacancies (OVs) defect in metal oxide-based photocatalysts play crucial role in improving their charge carrier separation efficiencies to enhance their photocatalytic performances. In this work, OVs were introduced in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
5
11
0
Order By: Relevance
“…The stacking mode between the sheets is changed; thus, the three-dimensional space of 5-CBMOS is significantly stronger than that of BMOS. It assists in exposing more catalytic active sites, which is beneficial for the adsorption and activation of O 2 and reactants. , Figure e is the TEM image of 5-CBMOS, showing the ultrathin sheet structure, which is consistent with the SEM results. The crystal structure of 5-CBMOS is further magnified, and the lattice fringes with a spacing of 0.274 nm correspond to the {002} crystal plane of the orthorhombic phase Bi 2 MoO 6 (Figure f). , Energy-dispersive X-ray spectroscopy (TEM–EDX) results of the prepared samples indicate that Bi, Ce, Mo, and O elements contained in 5-CBMOS are uniformly distributed in the matrix material (Figure g), which further confirm the successful synthesis of the Ce-doped Bi 2 MoO 6 composite.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The stacking mode between the sheets is changed; thus, the three-dimensional space of 5-CBMOS is significantly stronger than that of BMOS. It assists in exposing more catalytic active sites, which is beneficial for the adsorption and activation of O 2 and reactants. , Figure e is the TEM image of 5-CBMOS, showing the ultrathin sheet structure, which is consistent with the SEM results. The crystal structure of 5-CBMOS is further magnified, and the lattice fringes with a spacing of 0.274 nm correspond to the {002} crystal plane of the orthorhombic phase Bi 2 MoO 6 (Figure f). , Energy-dispersive X-ray spectroscopy (TEM–EDX) results of the prepared samples indicate that Bi, Ce, Mo, and O elements contained in 5-CBMOS are uniformly distributed in the matrix material (Figure g), which further confirm the successful synthesis of the Ce-doped Bi 2 MoO 6 composite.…”
Section: Resultssupporting
confidence: 80%
“…By comparing the SEM images of BMOS and 5-CBMOS, Ce doping has few effects on the thickness, but it can make the sheet size of Bi 2 MoO 6 increase slightly.The stacking mode between the sheets is changed; thus, the threedimensional space of 5-CBMOS is significantly stronger than that of BMOS. It assists in exposing more catalytic active sites, which is beneficial for the adsorption and activation of O 2 and reactants 42,43. Figure1eis the TEM image of 5-CBMOS, showing the ultrathin sheet structure, which is consistent with the SEM results.…”
supporting
confidence: 82%
“…Notably, compared to various conventional processes and advanced oxidation processes, “heterogeneous photocatalysis” , is considered to be a more viable option for degradation of antibiotics without the use of any exogenous supply of H 2 O 2 . This is a “green approach”, where semiconductor-type photocatalysts upon absorbing light of energy greater than its band gap can in situ generate a plethora of reactive oxygen species (ROS), for example, hydroxyl radicals, superoxide radicals, singlet oxygen, and H 2 O 2 . , It was noted in the literature that the nanocomposites (NCs) made of other metal oxide systems with carbonaceous materials, for example, N-doped carbon-coated mulberry-like cobalt manganese oxide (H-CoMnO x @NC) as a photo-Fenton-like catalyst, has shown excellent results for removal of seven different pharmaceutically active compounds . However, TiO 2 and ZnO nanoparticles (NPs) are most widely used photocatalysts owing to excellent photocatalytic performance, high chemical stability, and non-toxic nature. They are both wide band gap materials, which necessitate the use of UV light for photoexcitation.…”
Section: Introductionmentioning
confidence: 99%
“…This is a "green approach", where semiconductor-type photocatalysts upon absorbing light of energy greater than its band gap can in situ generate a plethora of reactive oxygen species (ROS), for example, hydroxyl radicals, superoxide radicals, singlet oxygen, and H 2 O 2 . 9,10 It was noted in the literature that the nanocomposites (NCs) made of other metal oxide systems with carbonaceous materials, for example, N-doped carbon-coated mulberry-like cobalt manganese oxide (H-CoMnO x @NC) as a photo-Fenton-like catalyst, has shown excellent results for removal of seven different pharmaceutically active compounds. 11 and non-toxic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Bi vacancy and Bi interstitial contained in Bi 2 MoO 6 were synthesized by Zhang et al exhibiting higher photoexcitation. Significantly, the single V O defect in Bi 2 MoO 6 is more importantly studied due to its relatively lower formational energy. , Huang et al synthesized different amounts of V O in Bi 2 MoO 6 with the higher tetracycline degradation rate of Bi 2 MoO 6 . Bai et al calcined Bi 2 MoO 6 at 450 °C and found that it exhibited much higher photocatalytic performance owing to the existence of V O .…”
Section: Introductionmentioning
confidence: 99%